Rapid microwave activation of waste palm into hierarchical porous carbons for supercapacitors using biochars from different carbonization temperatures as catalysts. Issue 34 (20th June 2019) - Liu, Chaozheng; Chen, Weimin; Li, Meichun; Hong, Shu; Li, Wanzhao; Pan, Mingzhu; Wu, Qinglin; Mei, Changtong
Abstract : A rapid, simple and cost-effective approach to prepare hierarchical porous carbons (PCs) for supercapacitors is reported by microwave activation of abundant and low-cost waste palm, biochar (BC) and KOH. Abstract : A rapid, simple and cost-effective approach to prepare hierarchical porous carbons (PCs) for supercapacitors is reported by microwave activation of abundant and low-cost waste palm, biochar (BC) and KOH. BCs from waste palm at different carbonization temperatures (300–700 °C), as catalysts and microwave receptors, were used here for the first time to facilitate the conversion of waste palm into hierarchical PCs. As a result, the high-graphitization PC obtained at a BC carbonization temperature of 300 °C (PC-300) possessed a high surface area (1755 m 2 g −1 ), a high pore volume (0.942 cm 3 g −1 ) and a moderate mesoporosity (37.79%). Besides their high-graphitization and hierarchical porous structure, the oxygen doping in PC-300 can also promote the rapid transport of electrolyte ions. The symmetric supercapacitor based on the PC-300 even in PVA/LiCl gel electrolyte exhibited a high specific capacitance of 164.8 F g −1 at a current density of 0.5 A g −1 and retained a specific capacitance of 121.3 F g −1 at 10 A g −1, demonstrating a superior rate capacity of 73.6%. Additionally, the PC-300 supercapacitor delivered a high energy density of 14.6 W h kg −1 at a power density of 398.9 W kg −1 and maintained an energy density of 10.8 W h kg −1 at a high power density of 8016.5 W kg −1, as well as an excellent cycling stability after 2000 cycles with a capacitance retention of 92.06%.